2019
DOI: 10.3390/ijms20153649
|View full text |Cite
|
Sign up to set email alerts
|

Ionizing Radiation Increases the Activity of Exosomal Secretory Pathway in MCF-7 Human Breast Cancer Cells: A Possible Way to Communicate Resistance against Radiotherapy

Abstract: Radiation therapy, which applies high-energy rays, to eradicate tumor cells, is considered an essential therapy for the patients with breast cancer. Most tumor cells secrete exosomes, which are involved in cell-to-cell communication in tumor tissue and contribute therapeutic resistance and promote tumor aggressiveness. Here, we investigated the effect of clinically applicable doses of X-ray irradiation (2, 4, 6, 8, 10 Gy) on the dynamics of the exosomes’ activity in MCF-7 breast cancer cells. Survival and apop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
83
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 89 publications
(84 citation statements)
references
References 56 publications
1
83
0
Order By: Relevance
“…Exosomes mediate various physiologic processes by transmitting their contents, such as nucleic acids, proteins and lipids to recipient cells, therefore exerting their functions. 25,26 For example, mouse colon cancer cell-derived exosomes carry Wnt1 to mediate autophagic ux and tumorigenic potential. 24 miR-192-5p was shown within exosomes derived from lipotoxic hepatocyte to activate the macrophages.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Exosomes mediate various physiologic processes by transmitting their contents, such as nucleic acids, proteins and lipids to recipient cells, therefore exerting their functions. 25,26 For example, mouse colon cancer cell-derived exosomes carry Wnt1 to mediate autophagic ux and tumorigenic potential. 24 miR-192-5p was shown within exosomes derived from lipotoxic hepatocyte to activate the macrophages.…”
Section: Discussionmentioning
confidence: 99%
“…The typical exosome marker ALIX is a transcription factor, and is involved in exosome biogenesis and secretion. 26 Through the knockdown of ALIX, exosome production and secretion decreased. Our results revealed that ALIX knockdown altered the effect of macrophagederived exosomes on cell proliferation, migration and drugresistance.…”
Section: Discussionmentioning
confidence: 99%
“…The use of radiation therapy in the treatment of a variety of CNS-related malignancies can affect brain structure and function, leading to cognitive deterioration [102]. Radiation used in cancer therapy can also activate the biogenesis and induce exosome secretion from cancer cells [103]. Hinzman et al highlighted that several molecules (i.e., triglycerides, platelet activating factor, carnitine, and C-16 sphinganine) involved in inflammation were enriched in the exosomes of mice exposed to cranial ionizing radiation [104].…”
Section: Cancer-therapy-derived Exosomes and Cognitive Impairmentmentioning
confidence: 99%
“…There are nevertheless a number of potential disadvantages to some of the aforementioned methods. The use of additives such as ionomycin and calcium phosphate, for example, while capable of enhancing exosome yield by 2.5-fold within 2-72 h (approximately 0.03-1-fold/h), are, however, dose dependent and overexposure of the cells to these chemicals can lead to a considerable reduction in their viability 34 ; similarly, exposing cells to ionising radiation can result in cell apoptosis 46 . Thermal and oxidative stresses, on the other hand, have been reported to increase exosome yield by approximately 20-30-fold in 24 h (approximately 0.8-1.25-fold/h) but can generate immunoresponsive exosomes, which could impair their diagnostic or therapeutic potential 44 .…”
mentioning
confidence: 99%